Task‐based human‐structured research data interaction: A discipline independent examination. Issue 1 (22nd October 2020) - Xiao, Fanghui; Ma, Rongqian; He, Daqing
Abstract: With the development of open data movement, an increasing number of structured research datasets (SRD) are available online due to the successful data infrastructure and the strong demand for sharing data. Yet there still lacks a thorough, systematic investigation of researcher‐SRD interactions, which is important to understand users' needs, challenges, and expectations. Our work extends from the current scholarship and proposes a task‐based approach to examining how researchers interact with SRD, without considering individual disciplines. This study identifies two types of research tasks, the data‐driven tasks and model‐driven tasks, and also proposes a framework for researcher‐SRD interaction. Our findings will contribute to the research field of human data behaviors.